CXCR2 signaling promotes secretory cancer‐associated fibroblasts in pancreatic ductal adenocarcinoma. Issue 7 (26th May 2020) - Awaji, Mohammad; Saxena, Sugandha; Wu, Lingyun; Prajapati, Dipakkumar R.; Purohit, Abhilasha; Varney, Michelle L.; Kumar, Sushil; Rachagani, Satyanarayana; Ly, Quan P.; Jain, Maneesh; Batra, Surinder K.; Singh, Rakesh K.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) remains one of the most challenging malignancies. Desmoplasia and tumor‐supporting inflammation are hallmarks of PDAC. The tumor microenvironment contributes significantly to tumor progression and spread. Cancer‐associated fibroblasts (CAFs) facilitate therapy resistance and metastasis. Recent reports emphasized the concurrence of multiple subtypes of CAFs with diverse roles, fibrogenic, and secretory. C‐X‐C motif chemokine receptor 2 (CXCR2) is a chemokine receptor known for its role during inflammation and its adverse role in PDAC. Oncogenic Kras upregulates CXCR2 and its ligands and, thus, contribute to tumor proliferation and immunosuppression. CXCR2 deletion in a PDAC syngeneic mouse model produced increased fibrosis revealing a potential undescribed role of CXCR2 in CAFs. In this study, we demonstrate that the oncogenic Kras‐CXCR2 axis regulates the CAFs function in PDAC and contributes to CAFs heterogeneity. We observed that oncogenic Kras and CXCR2 signaling alter CAFs, producing a secretory CAF phenotype with low fibrogenic features; and increased secretion of pro‐tumor cytokines and CXCR2 ligands, utilizing the NF‐κB activity. Finally, using syngeneic mouse models, we demonstrate that oncogenic Kras is associated with secretory CAFs and that CXCR2 inhibition promotes activation of fibrotic cells (myofibroblasts) and impact tumors in a mutation‐dependent manner.